Constitutional Guarantees of Freedom of Speech and the Right to Access Information on the Internet - ALTYNBEKKYZY, Alua; ZHUMABAEVA, Galiya Amangeldinovna (Journal of Advanced Research in Law and Economics, 2019)
The article deals with the constitutional regulation of freedom of speech and access to information in the infosphere of the Internet. The aim of the presented work is a comprehensive study of the implementation of the constitutional freedom of speech and the right to access information on the Internet in their logical relationship. To achieve this goal, the authors examine the concept and reveal the constitutional legal meaning of freedom of speech, identify and explore the main features of the implementation of the constitutional freedom of speech on the Internet and indicate the levels of regulation of constitutional legal freedom of speech on the Internet. The provisions advocated by the authors, their conclusions and proposals on the application of international experience can be used in the preparation of amendments to the current legislation of Kazakhstan on the regulation of the information sphere.